TMAO Aggregates Neurological Damage Following Ischemic Stroke by Promoting Reactive Astrocytosis and Glial Scar Formation via the Smurf2/ALK5 Axis - Su, Haibo; Fan, Shaoping; Zhang, Lingqiong; Qi, Hui (Frontiers in Cellular Neuroscience, 2021)
Ischemic stroke has been reported to cause significant changes to memory, thinking, and behavior. Intriguingly, recently reported studies have indicated the association of Trimethylamine N-oxide (TMAO) with the acute phase of ischemic stroke. However, the comprehensive underlying mechanism remained unknown. The objective of the present study was to investigate the association between TMAO and recovery of neurological function after ischemic stroke. For this purpose, a middle cerebral artery occlusion/reperfusion (MCAO/R) rat model was established and treated with TMAO or/and sh-ALK5, followed by the neurological function evaluation. Behaviors of rats were observed through staircase and cylinder tests. Moreover, the expression of Smurf2 and ALK5 was detected by immunohistochemistry while expression of GFAP, Neurocan, and Phosphacan in brain tissues was determined by immunofluorescence. Thereafter, gain- and loss-of-function assays in astrocytes, the proliferation, viability, and migration were evaluated by the EdU, CCK-8, and Transwell assays. Besides, Smurf2 mRNA expression was determined by the RT-qPCR, whereas, Smurf2, ALK5, GFAP, Neurocan, and Phosphacan expression was evaluated by the Western blotting. Finally, the interaction of Smurf2 with ALK5 and ALK5 ubiquitination was assessed by the co-immunoprecipitation. Notably, our results showed that TMAO promoted the proliferation of reactive astrocyte and formation of glial scar in MCAO/R rats. However, this effect was abolished by the Smurf2 overexpression or ALK5 silencing. We further found that TMAO upregulated the ALK5 expression by inhibiting the ubiquitination role of Smurf2. Overexpression of ALK5 reversed the inhibitory effect of Smurf2 on astrocyte proliferation, migration, and viability. Collectively, our work identifies the evolutionarily TMAO/Smurf2/ALK5 signaling as a major genetic factor in the control of reactive astrocyte proliferation and glial scar formation in ischemic stroke, thus laying a theoretical foundation for the identification of ischemic stroke.